Assessment of impact of priority movement for urban public passenger transport on the quality of passenger service - Vdovychenko, Volodymyr; Ivanov, Igor; Pidlubnyi, Serhii; Vasyliev, Mykyta; Вдовиченко, Володимир Олексійович; Іванов, Ігор Євгенович; Підлубний, Сергій Юрійович; Васильєв, Микита Костянтинович (Харківський національний автомобільно-дорожній університет, 2023)
Problem. The article presents a view on solving the problem of the management formation measures to improve the quality of public transport services through the feasibility justification of im plementing priority movement of urban public passenger transport in relation to the assessment of pas sengers' perception of the actual travel time along the route. Goal. The purpose of the work is to estab lish a characteristic relationship between the traffic parameters of route vehicles in the conditions of the priority of urban public passenger transport and time indicators of the quality assessment of pas senger transport services. Method. The methodological basis for establishing a connection between traffic parameters in terms of the priority of urban public passenger transport and time indicators for evaluating the quality of transport service is a set of developed analytical models that describe the process of formation of passenger exchange at stopping points and time parameters of vehicle move ment. Results. On the basis of the functional connection for the selected structure of the research object, it was established that the implementation of the urban public passenger transport priority with the organization of traffic on special lanes and unhindered passage of regulated intersections plays a sig nificant role in improving the quality of passenger transport services. Originality. The assessment of the quality of transport service is based on establishing the level of compliance of each passenger's actual travel time with the previously planned. The use of travel time as a primary evaluation indicator is due to its leading role in the formation of quality criteria and the presence of influence on the param eters that determine the level of transport supply on the route. Practical meaning. The distribution of passengers at stops on route No. 24 «micro-district 602 – Akademika Pavlova subway st.» (Kharkiv, Ukraine) was obtained during modeling between the levels of perception of the quality of transport service showed that for everyday conditions, 8.9% and 27.8% of passengers (36.7% in total) receive a high-quality and suitable assessment, for traffic priority by sections – 32.3% and 64% (96.3% in total), when organizing priority passage at the intersection – 57.5% and 40.4% (97.9% in total). The obtained results indicate the expediency of implementing priority traffic from the standpoint of assessing the level of improvement in the quality of passenger service.
Оцінка впливу пріоритетного руху міського громадського пасажирського транспорту на якість обслуговування пасажирів
Keywords: urban public passenger transport; quality of transport service; priority traffic; міський громадський пасажирський транспорт; якість транспортного обслуговування; пріоритетний рух; 656.072; 10.30977/AT.2219-8342.2023.52.0.06